Knowledge and attitudes regarding HPV infection and its vaccination among adolescent girls in Chandannath municipality, Jumla, Nepal - Thapa, Savina; Thapa, Nabin; Bahadur Rokaya, Yagya; Mani Giri, Rajendra; Kumar Sharma, Sandeep; Lama, Monika; Joshi, Sanjeev; Singh, Lokjan; Rokaya, Manish (Journal of Chitwan Medical College, 2025)
Introduction: Human papillomavirus (HPV) is a major global health concern and the primary cause of cervical cancer and death. This study aimed to assess the knowledge and attitudes regarding HPV infection and its vaccination among adolescent girls in Chandannath Municipality, Jumla, Nepal. Method: A descriptive cross-sectional design was conducted among selected adolescent girls aged 13-19 years in selected schools within Chandannath Municipality, Jumla, Nepal. A proportionate sampling technique was used to select students from grades 9-12. A structured self-administered questionnaire was used to collect data. Data were entered and analysed using SPSS version 16. Data were analysed using descriptive statistics, and Chi-square tests were applied to assess associations between variables. A p-value of ≤a0.05 was considered statistically significant. Result: Out of 422, majority of adolescent girl students, 280(66.4%), had poor knowledge of HPV infection and vaccination. Over half of the respondents, 224(52.8%), exhibited a favourable attitude toward HPV infection and vaccination. Poor knowledge was significantly associated with age 16–19 years (p=0.028), Hindu religion (p=0.021), maternal illiteracy (p=0.040), and low economic status (p=0.014). Favourable attitudes were significantly associated with age 16–19 years (p=0.012), religion (p=0.047), and father’s occupation (p=0.049). A strong positive association was found between knowledge and attitude (p<0.001). Conclusion: Two-thirds of adolescent girl students exhibited poor knowledge about HPV infection and vaccination, with notable gaps and varying attitudes observed. These findings emphasise the need for targeted educational initiatives and awareness campaigns for cervical cancer prevention.